Quantitative imaging biomarkers of coronary plaque morphology: insights from EVAPORATE - Buckler, Andrew J.; Doros, Gheorghe; Kinninger, April; Lakshmanan, Suvasini; Le, Viet T.; Libby, Peter; May, Heidi T.; Muhlestein, Joseph B.; Nelson, John R.; Nicolaou, Anna; Roy, Sion K.; Shaikh, Kashif; et al. (Frontiers in Cardiovascular Medicine, 2023)
Aims: Residual cardiovascular risk persists despite statin therapy. In REDUCE-IT, icosapent ethyl (IPE) reduced total events, but the mechanisms of benefit are not fully understood. EVAPORATE evaluated the effects of IPE on plaque characteristics by coronary computed tomography angiography (CCTA). Given that the conclusion that IPE-treated patients demonstrate that plaque burden decreases has already been published in the primary study analysis, we aimed to demonstrate whether use of an analytic technique defined and validated in histological terms could extend the primary study in terms of whether such changes could be reliably seen in less time on drug, at the individual (rather than only at the cohort) level, or both, as neither of these were established by the primary study result.Methods and Results: EVAPORATE randomized patients to IPE 4 g/d or placebo. Plaque morphology, including lipid-rich necrotic core (LRNC), fibrous cap thickness, and intra-plaque hemorrhage (IPH) were assessed using ElucidVivo ® (Elucid Bioimaging Inc.) on CCTA. Changes in plaque morphology between treatment groups were analyzed. A neural network to predict treatment assignment was used to infer patient representation that encodes meaningful morphological changes. Fifty-five patients completed the 18-month visit in EVAPORATE with interpretable images at each of the three time points. The decrease of LRNC between patients on IPE vs. placebo at 9 months (reduction of 2 vs. an increase of 41 mm 3 , p=0.008), widening at 18 months (6 vs. 58 mm 3 increase, p=0.015). While not statistically significant on a univariable basis, reductions in wall thickness and increases in cap thickness motivated multivariable modeling on an individual patient basis. Perpatient response assessment was possible using a multivariable model of lipid-rich phenotype at 9month follow-up, p<0.01 (sustained at 18 months), generalizing well to a validation cohort.Conclusion: Plaques in IPE-treated patients acquired more characteristics of stability. Reliable assessment using histologically-validated analysis of individual response is possible at 9-months, with sustained stabilization at 18-months, providing a quantitative basis to elucidate drug mechanism and assess individual patient response.